Hooked - Wise, A. C. (Titan Books, 2022)
"Once invited, always welcome. Once invited, never free. Captain James Hook, the immortal pirate of Neverland, died a thousand times. He was drowned, stabbed by Peter Pan's sword, eaten by the beast swimming below the depths, but every time he was resurrected by one boy's dark imagination. Until he found a door in the sky, an escape. And he took the chance no matter the cost. Now in London twenty-two years later, James passes his days with opium to suppress the ghosts that haunt him. But in a moment of weakness, he reaches back through his dreams to Neverland and something slips through the open door between worlds. Peter Pan's beast has been waiting a long time for Captain Hook and now it's hunting him, leeching the life from anybody in its way. But a chance encounter leads James to another survivor of Neverland. Wendy Darling, now a grown woman, is the only one who knows how dark a shadow Neverland casts, no matter how far you run. To vanquish Pan's monster once and for all, Hook must play the villain one last time..." -- Back cover.